Cognitive Training for Post-Acute Traumatic Brain Injury: A Systematic Review and Meta-Analysis - Hallock, Harry; Collins, Daniel; Lampit, Amit; Deol, Kiran; Fleming, Jennifer; Valenzuela, Michael (Frontiers in Human Neuroscience, 2016)
Objective: To quantitatively aggregate effects of cognitive training (CT) on cognitive and functional outcome measures in patients with traumatic brain injury (TBI) more than 12-months post-injury. Design: We systematically searched six databases for non-randomized and randomized controlled trials (RCTs) of CT in TBI patients at least 12-months post-injury reporting cognitive and/or functional outcomes. Main Measures: Efficacy was measured as standardized mean difference (Hedges’ g) of post-training change. We investigated heterogeneity across studies using subgroup analyses and meta-regressions. Results: Fourteen studies encompassing 575 patients were included. The effect of CT on overall cognition was small and statistically significant (g=0.22, 95%CI 0.05 to 0.38; p=0.01), with low heterogeneity (I2=11.71%) and no evidence of publication bias. A moderate effect size was found for overall functional outcomes (g=0.32, 95%CI 0.08 to 0.57, p=0.01) with low heterogeneity (I2=14.27%) and possible publication bias. Statistically significant effects were also found only for executive function (g=0.20, 95%CI 0.02 to 0.39, p=0.03) and verbal memory (g=0.32, 95%CI 0.14 to 0.50, p<0.01). Conclusions: Despite limited studies in this field, this meta-analysis indicates that CT is modestly effective in improving cognitive and functional outcomes in patients with post-acute TBI and should therefore play a more significant role in TBI rehabilitation.